Down-regulation of microRNA-182 and microRNA-183 predicts progression of osteosarcoma - Golbakhsh, Mohammad Reza (Arch Med Sci, 2016)
INTRODUCTION: The aim of this study was to investigate the expression levels of microRNA-182 and microRNA-183 and their association with clinicopathological features in patients with osteosarcoma. MATERIAL AND METHODS: Total RNA was purified from samples and noncancerous bone tissues and then quantitative real-time polymerase chain reaction was applied to evaluate the expression levels of microRNAs, and their relationship with clinicopathological features and survival in osteosarcoma patients. RESULTS: Our findings showed that expression of MiR-182 was clearly lower in osteosarcoma bone tissue (mean ± SD: 2.84 ±.07) compared with noncancerous bone tissues (6.23 ±1.72, p = 0.004). On the other hand, lower expression of MiR-183 was seen in osteosarcoma bone tissue (1.43 ±0.59) when compared with normal tissues (4.36 ±2.47, p = 0.036). Decreased expression of MiR-182 was clearly correlated with advanced clinical stage (p = 0.001), metastasis or recurrence (p = 0.024), and large tumor size (p = 0.032). Decreased expression of MiR-183 was associated with advanced TNM stage (p = 0.004), and metastasis or recurrence (p = 0.002). A multivariate Cox proportional hazards model revealed that low expression of MiR-182 and MiR-183 (p = 0.02; p = 0.016), TNM stage (p = 0.04), and metastasis or recurrence (p = 0.03) were significantly associated with poor survival as independent prognostic factors. CONCLUSIONS: These findings suggest that MiR-182 and MiR-183 may be associated with progression and metastasis of osteosarcoma.